Modeling of the Potential Geographical Distribution of Three Fritillaria Species Under Climate Change - Jiang, Ruiping; Zou, Meng; Qin, Yu; Tan, Guodong; Huang, Sipei; Quan, Huige; Zhou, Jiayu; Liao, Hai (Frontiers in Plant Science, 2022)
Fritillaria species, as well known Chinese traditional medicine for more than 2000 years, have become rare resources due to excessive harvesting. In order to balance the economical requirement and ecological protection of Fritillaria species, it is necessary to determine (1) the important environmental variables that were responsible for the spatial distribution, (2) distribution change in response to climate change in the future, (3) ecological niche overlap between various Fritillaria species, and (4) the correlation between spatial distribution and phylogenies as well. In this study, the areas with potential ecological suitability for F. cirrhosa, F. unibracteata and F. przewalskii were predicted using MaxEnt based on current occurrence records and bioclimatic variables. The result indicated that precipitation and elevation were the most important environmental variables for three species. Moreover, the current suitable habitats of F. cirrhosa, F. unibracteata and F. przewalskii encompassed 681,951, 481,607 and 349,199 km2, respectively. Under scenario of highest concentration of greenhouse gas emission (SSP585), the whole suitable habitats of F. cirrhosa and F. przewalskii reaches the maximum from 2021 to 2100, while those of F. unibracteata reach the maximum from 2021 to 2100 under scenario of moderate emission (SSP370) from 2021 to 2100. The MaxEnt data was also used to predict ecological niche overlap, and thus high overlap occurring among three Fritillaria species was observed. The niche overlap of three Fritillaria species was related to the phylogenetic analysis despite the non-significance (P > 0.05), indicating that spatial distribution was one of the factors that contributed to the speciation diversification. Additionally, we predicted species-specific habitat to decrease habitat competition. Overall, the information obtained in this study provided new sight on the potential distribution and ecological niche of three species for the conservation and management in the future.